Investigating musculoskeletal pain and frailty in an ageing population - Chaplin, Wendy (2025)
Background: Frailty is defined as a vulnerability state with decreased physiological reserve observed in older people. Frailty may be characterised by a loss of homeostatic resilience due to multi-organ, age-associated decline. People with frailty have an elevated susceptibility to stressors and/or disproportionate response to challenges; this leads to a significant functional decline and increased risk of adverse health outcomes.